Screening and Identification of Alkaloid Compounds in Kayu Kuning Stem (Arcangelisia Flava Merr) - Restu Kartiko Widi; Titin Indriati (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
Extraction of kayu kuning stem (Arcangelisia flava Merr) with petroleum ether, chloroform and methanol 80% to screen of alkaloid compound has been carried out. Extract of chloroform was added by 10% of NH3 solution and Al2O3, then put into column chromatography and flowed by chloroform. Eluat was tested by dragendorf reagant to know the present of the alkaloid compound. This eluat was identified by thin layer chromatography with chloroform-methanol (1:4 v/v) as a mobile phase. It gave four spots that had the Rf value of 0.78; 0.64; 0.41; 0.18. After these spots were added by dragendorf reagant, only the first spot gave positive result. Then the chloroform fraction was separated by column chromatography to take the fraction which had Rf value of about 0.78 and thenit was analyzed by spectroscopic method (uv-vis and infra red). The data suggested that the alkaloid compound was the pyridin alkaloids group.